2003
DOI: 10.1007/bf03019375
|View full text |Cite
|
Sign up to set email alerts
|

Une méthode antérieure combinée utilisant un seul site d’injection cutanée permet l’anesthésie des membres inférieurs chez des patients en décubitus dorsal

Abstract: P Pu ur rp po os se e: : Lower limb anesthesia (LLA) requires the combination of, at least, three-in-one and sciatic nerve (SCN) blocks. Anterior approaches are easier to perform with minimal discomfort in supine patients, specially for traumatology. Feasibility of a single needle entry combined approach is reported.C Cl li in ni ic ca al l f fe ea at tu ur re es s: : The combined landmark was applied in 119 ASA I and II patients (32-68 yr) scheduled for surgery below the knee. Needle (nerve stimulation applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…In terms of motor block ending times, no difference was observed at hours 1, 2 or 4, although a significantly prolonged motor block time was observed in the alkalinized group at hours 6 and 12. This difference disappeared at 24 h. Mean motor block ending times were 12.54 h and 18.96 h in our groups and were similar to those reported by Pandin et al 8 The latest block ending times were hours 22 and 24, respectively. Our results suggest that alkalinization does not have unwanted consequences such as motor blocks over 24 h.…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of motor block ending times, no difference was observed at hours 1, 2 or 4, although a significantly prolonged motor block time was observed in the alkalinized group at hours 6 and 12. This difference disappeared at 24 h. Mean motor block ending times were 12.54 h and 18.96 h in our groups and were similar to those reported by Pandin et al 8 The latest block ending times were hours 22 and 24, respectively. Our results suggest that alkalinization does not have unwanted consequences such as motor blocks over 24 h.…”
Section: Figuresupporting
confidence: 92%
“…Motor block was evaluated using the Bromage Scale (BS) (0: no motor block, 1: hip flexion normal but weak knee and ankle movements, 2: weak hip and knee movements, normal ankle movement, 3: weak hip, knee and ankle movements). 8 In the BS test, 2 and 3 are regarded as sufficient values. Cases determined as sufficient in terms of sensorimotor block were operated on at the end of 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…A new single position supine approach to sciatic and femoral nerve block was described by Raj et al 11 However the lithotomy position which they described was difficult to be achieved in patients with limited mobility. Pierre Pandin et al 12 proposed the single injection technique for the combined 3 in 1 block and sciatic nerve block. From the needle injection point described, the needle was directed caudad and laterally to perform the sciatic nerve block; and then directed cephalad and medially to locate the femoral nerve.…”
Section: Resultsmentioning
confidence: 99%
“…In a metaanalysis of eight randomized controlled trials including 379 patients, it was reported that the addition of sciatic nerve block to femoral nerve block in TKA significantly reduces postoperative pain and opioid consumption 11,12 . USG guided anterior sciatic nerve block in addition to femoral nerve block can be safely applied in arthroscopic knee surgeries, knee surgeries, and in patients with high comorbidity, the application of other anesthesia methods is at high risk, and it has also been reported that this block provides effective postoperative analgesia [13][14][15] . In our study, we preferred the anterior sciatic nerve block owing to its ease of administration and better tolerability by patients, and this block does not require a special position, unlike other sciatic nerve block approaches.…”
Section: Discussionmentioning
confidence: 99%